R-loop-induced irreparable DNA damage evades checkpoint detection in the C. elegans germline. Issue 14 (25th July 2022) - Hicks, Tara; Koury, Emily; McCabe, Caleb; Williams, Cameron; Crahan, Caroline; Smolikove, Sarit
Abstract: Accumulation of DNA–RNA hybrids in the form of R-loops can result in replication–transcription conflict that leads to the formation of DNA double strand breaks (DSBs). Using null mutants for the two Caenorhabditis elegans genes encoding for RNaseH1 and RNaseH2, we identify novel effects of R-loop accumulation in the germline. R-loop accumulation leads, as expected, to replication stress, followed by the formation of DSBs. A subset of these DSBs are irreparable. However, unlike irreparable DSBs generated in other systems, which trigger permanent cell cycle arrest, germline irreparable DSBs are propagated to oocytes. Despite DNA damage checkpoint activation in the stem cell niche, the signaling cannot be sustained and nuclei with irreparable DNA damage progress into meiosis. Moreover, unlike other forms of DNA damage that increase germline apoptosis, R-loop-generated DSBs remain undetected by the apoptotic checkpoint. This coincides with attenuation of ATM/ATR signaling in mid-to-late meiotic prophase I. These data altogether indicate that in the germline, DSBs that are generated by R-loops can lead to irreparable DSBs that evade cellular machineries designed for damage recognition. These studies implicate germline R-loops as an especially dangerous driver of germline mutagenesis.